Effect of the myeloperoxidase inhibitor AZD3241 on microglia: a PET study in Parkinson’s disease - Jucaite, Aurelija; Svenningsson, Per; Rinne, Juha O.; Cselényi, Zsolt; Varnäs, Katarina; Johnström, Peter; Amini, Nahid; Kirjavainen, Anna; Helin, Semi; Minkwitz, Margaret; Kugler, Alan R.; Posener, Joel A.; et al. (Brain (London, England : 1878), 2015)
Impaired mitochondrial function, oxidative stress and formation of excessive levels of reactive oxygen species play a key role in neurodegeneration in Parkinson's disease. Myeloperoxidase is a reactive oxygen generating enzyme and is expressed by microglia. The novel compound AZD3241 is a selective and irreversible inhibitor of myeloperoxidase. The hypothesized mechanism of action of AZD3241 involves reduction of oxidative stress leading to reduction of sustained neuroinflammation. The purpose of this phase 2a randomized placebo controlled multicentre positron emission tomography study was to examine the effect of 8 weeks treatment with AZD3241 on microglia in patients with Parkinson's disease. Parkinson patients received either AZD3241 600 mg orally twice a day or placebo (in 3:1 ratio) for 8 weeks. The binding of (11)C-PBR28 to the microglia marker 18 kDa translocator protein, was examined using positron emission tomography at baseline, 4 weeks and 8 weeks. The outcome measure was the total distribution volume, estimated with the invasive Logan graphical analysis. The primary statistical analysis examined changes in total distribution volume after treatment with AZD3241 compared to baseline. Assessments of safety and tolerability of AZD3241 included records of adverse events, vital signs, electrocardiogram, and laboratory tests. The patients had a mean age of 62 (standard deviation = 6) years; 21 were male, three female and mean Unified Parkinson's Disease Rating Scale III score (motor examination) ranged between 6 and 29. In the AD3241 treatment group (n = 18) the total distribution volume of (11)C-PBR28 binding to translocator protein was significantly reduced compared to baseline both at 4 and 8 weeks (P < 0.05). The distribution volume reduction across nigrostriatal regions at 8 weeks ranged from 13-16%, with an effect size equal to 0.5-0.6. There was no overall change in total distribution volume in the placebo group (n = 6). AZD3241 was safe and well tolerated. The reduction of (11)C-PBR28 binding to translocator protein in the brain of patients with Parkinson's disease after treatment with AZD3241 supports the hypothesis that inhibition of myeloperoxidase has an effect on microglia. The results of the present study provide support for proof of mechanism of AZD3241 and warrant extended studies on the efficacy of AZD3241 in neurodegenerative disorders.